Red Meat Science and Production Volume 2. Intrinsic Meat Character - Holloway, Joseph William; Wu, Jianping; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprehensively describes the biological underpinnings of red meat production, discussing the current state of the science in the context of the provision of red meat products perceived by consumers to offer a quality eating experience. Covering advances in the science of red meat production, it focuses on production system elements that affect product quality. The chapters explore the latest developments in the determination of consumer preferences, and interpret of these preferences in terms of quality characteristics of red meat, investigating the science-based orchestration of red meat production to achieve product consistency. The book highlights topics such as consumer preferences, the biological and production system elements affecting red meat safety, and the intrinsic (appearance, aroma, and sensory quality) and extrinsic (humane animal and environmentally friendly production) characteristics of red meat. For each characteristic, it discusses the underlying biological and biochemical processes and examines means of altering production systems to impact consumer eating experiences. The book also features a perspective on creating holistic integrated systems for producing red meats to meet consumers' expectations around the globe. Written by leading authorities in the area of global red meat production systems, it is a comprehensive resource for consumer-oriented red meat producers. .
Introduction -- The Red Meat Consumer -- Safety -- Traceability -- Intrinsic Quality Factors: Carcass Quality Grading Systems -- Intrinsic Quality Factors: Aroma -- Intrensic Quality Factors: Tenderness -- Intrensic Quality Factors: Juiciness -- Intrensic Quality Factors: Flavor -- Extrinsic Quality Factors:Price -- Extrensic Quality Factors: Healthfulness -- Extrensic Quality Factors: Environmental Impact -- Extrensic Quality Factors: Humane Animal Management -- Meat By-products -- Integrated Global Red Meat.
Keywords: Food science; Biotechnology; Vertebrates; Food Science; Biotechnology; Vertebrate Zoology